Migration as Cultural Phenomenon in a Globalized World: A Pilot Study on Lifestyle and Eating Behaviours of Adolescents Living in Rome - Federica Intorre; Maria Stella Foddai; Eugenia Venneria (Adolescents, 2023)
The aim of this research was to assess, through an observational study, lifestyle and eating behaviours of adolescents (native, and first- and second-generation immigrants), in order to understand if the migration process may have influenced these aspects. The study was carried out by a structured questionnaire packet that investigated anthropometric data, eating habits, smoking, alcohol consumption, physical activity, and sedentary behaviours. A total of 105 respondents, aged 10–24 years (51.4% first-generation immigrants, 19.1% second-generation immigrants, and 29.5% natives) were included in the study. The results showed statistical differences in some social aspects by migration status, such as place of residence, living arrangement, parental educational level, and eating differently from family members. Despite these differences, volunteers were perfectly integrated regarding most eating habits and lifestyle behaviour, underlying a process of acculturation. Moreover, our study indicates the existence of inadequate dietary habits, such as skipping breakfast. It is important to implement effective nutrition interventions for adolescents to promote healthier lifestyle choices, considering that they should also include cultural components of dietary habits.